STRATEGI GURU DALAM MENINGKATKAN MINAT BELAJAR ANAK MELALUI CERITA TOKOH - Said, Alfan; Sofa Muthohar (LPPM STAI DARUSSALAM LAMPUNG, 2024)
This research aims to increase children's interest in learning through the story of the character of the Prophet's friend, namely Abu Bakar Ash-Shiddiq, and also to understand the story of the character by using the storytelling method with wayang characters for children at the Husna Jaya Ngaliyan Kindergarten, Semarang. The Abu Bakar story puppet media was chosen because it improves aspects of children's development in speaking skills and also trains thinking in the story. This research uses qualitative research methods and literature study. Qualitative research is research that attempts to explain, examine and link data obtained either textually or contextually into writing to gain clarity on the problems discussed. The results of this research, the Husna Jaya Kindergarten teacher, regarding the teacher's strategy in increasing children's interest in learning through character stories, the children were very interested in the story of Abu Bakar Ash-Shiddiq in the question and answer activity, namely in the recalling session. One of the children named Fadhil really liked the stories we told, and Fadhil was also able to answer our questions. And not only Fadhil, other children also liked the story of Abu Bakr and they really liked the song we sang, namely the song There are 4 Caliphs, Friends of the Prophet with the version